Gene expression in granulosa cells from small antral follicles from women with or without polycystic ovaries - Owens,LA; Kristensen,SG; Lerner,A; Christopoulos,G; Lavery,S; Hanyaloglu,AC; Hardy,K; Yding,Andersen C; Franks,S (Journal of Clinical Endocrinology and Metabolism, 2019)
CONTEXT: Polycystic ovary syndrome (PCOS) is the commonest cause of anovulation. A key feature of PCOS is arrest of follicles at the small-medium sized antral stage. OBJECTIVE AND DESIGN: To provide further insight into the mechanism of follicle arrest in PCOS, we profiled; (1) gonadotropin receptors; (2) characteristics of aberrant steroidogenesis, and (3) expression of anti-Mullerian hormone (AMH) and its receptor in granulosa cells (GCs) from unstimulated, human small antral follicles (hSAFs) and from granulosa-lutein cells (GLCs). SETTING: GCs from hSAFs were collected at the time of cryopreservation of ovarian tissue for fertility preservation and GLCs collected during oocyte aspiration before IVF/ICSI. PARTICIPANTS: hSAF GCs were collected from 31 women (98 follicles), 10 with polycystic ovaries (PCO) and 21 without. GLCs were collected from 6 women with PCOS and 6 controls undergoing IVF. MAIN OUTCOME MEASURES: Expression of the following genes: LHCGR, FSHR, AR, INSR, HSD3B2, CYP11A1, CYP19, STAR, AMH, AMHR2, FST, INHBA, INHBB in GCs and GLCs were compared between women with PCO and controls. RESULTS: GCs in hSAFs from PCO women showed higher expression of LHCGR in a subset (20%) of follicles. Expression of FSHR (p<0.05), AR (p<0.05), CYP11A1 (P<0.05) was lower, and expression of CYP19A1 (p<0.05), STAR (p<0.05), HSD3B2 (ns), INHBA (p<0.05) higher in PCO GCs. Gene expression in GL cells differed between women with and without PCOS but also differed from that in GCs. CONCLUSIONS: Follicle arrest in PCO is characterised in GCs by differential regulation of key genes involved in follicle growth and function.